Synthesis, characterization,reaction mechanism and theoreticalstudy of anntimicrobial inhibitor from heteroaromatics based thiosemicarbazone - Jori Roslan, Muhammad Qusyairi; Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi (2018)
Invasive fungal and bacteria diseases are the major cause of morbidity and mortality in the critically ill and imunocompromised patients.The impact of current situation was encouraged researcher to develop a better drug against microbial activity. Previous study has reported single prologue of heteroaromatic and thiosemicarbazide have the unique ability as biomimetics as well as active pharmacophore. This study is successfully synthesised through combination of both 2- acetylthiophene and thiosemicarbazide in one molecule structure to form 2-acetylthiophenethiosemicarbazone. Both experimental and theoretical approaches have been applied to comprehend its structure synthesised compound as well as computational drug design. Structure of synthesised compound was characterized using spectroscopy methods. Computational drug design was conducted to calculate the binding interaction between protein and inhibitor. Density Functional Theory (DFT) was used to calculate the chemical properties of title compound such as highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), chemical hardness, softness, energy gap, chemical potential, and Fukui functions. Solvent determination and predictive interaction element were confirmed using COSMO-RS method calculation. The synthesised compound was tested in vitro against two Gram-positive and one Gram-negative bacterial strains which areStaphylococcus aureus, Staphylococcus epidermidis and Klebsiella pneumonia respectively and a fungus Candida Albicans . Synthesis compound was found that susceptible with all Gram-positive bacterial strain and fungus while not to Gram-negative bacterial strain. The synthesised compound was evaluated the inhibition zone and showed that Staphylococcus epidermidiswas active at concentration 100μg/mL with 16±1.5mm while Staphylococcus Aureus at 50μg/mL with 15±2.0mm of inhibition zone. Candida Albicans showed the highest active activity at concentration 50μg/mL with 19±3.2mm.